Synergistic Modulation of Cellular Contractility by Mixed Extracellular Matrices - Aastha Kapoor; Shamik Sen (International Journal of Cell Biology)
The extracellular matrix (ECM) is known to provide various physicochemical cues in directing cell behavior including composition, topography, and dimensionality. Physical remodeling of the ECM has been documented in a variety of cancers. In breast cancer, the increased deposition of matrix proteins, their crosslinking, and alignment create a stiffer microenvironment that activates cell contractility and promotes cancer invasion. In this paper, we sought to study the collective influence of ECM composition and density on the contractile mechanics of human MDA-MB-231 cells making use of the recently established trypsin deadhesion assay. Using collagen and fibronectin-coated surfaces of varying density, we show that cell contractility is tuned in a density-dependent manner, with faster deadhesion on fibronectin-coated surfaces compared to collagen-coated surfaces under identical coating densities. The deadhesion responses are significantly delayed when cells are treated with the myosin inhibitor blebbistatin. By combining collagen and fibronectin at two different densities, we show that mixed ligand surfaces synergistically modulate cell contractility. Finally, we show that on fibroblast-derived 3D matrices that closely mimic in vivo matrices, cells are strongly polarized and exhibit faster deadhesion compared to the mixed ligand surfaces. Together, our results demonstrate that ECM composition, density, and 3D organization collectively regulate cell contractility.